Predictors of Food Web Resistance to Environmental Change - Javier Jarillo; Jonathan F. Jupke; Tom Sinclair; Lorraine Maltby; Ralf B. Schäfer; Frederik De Laender (Ecology Letters, 2026)
Impacts of environmental change on ecosystems are seemingly highly context‐dependent and contingent on details. Here, we provide mathematical and numerical evidence that there is some generality to the resistance of food webs to species loss. To this end, we mathematically analyse simple food web models, run simulations with randomly wired food webs, develop a spatially explicit meta‐community model for realistic macroinvertebrate communities inhabiting European streams, and analyse field data. These approaches jointly support three general rules for food web resistance: (1) all else equal, predators are more vulnerable than prey, and predator diversity declines before prey diversity; (2) food webs with higher prey diversity tend to be less resistant to environmental change; and (3) food web resistance decreases with the mean taxon tolerance and reaches a maximum at an optimal ratio of predator to prey tolerance. Our findings elucidate characteristics that make food webs vulnerable, fostering more effective conservation practices.

Monitoring Risso's Dolphins in the Northeast Atlantic: A Deep Learning Approach to Classify Echolocation Click Detections - Thomas Webber; Denise Risch; Gordon Hastie; Rona Sinclair; Suzanne Beck; Per Berggren; Oliver Boisseau; Katie Dyke; Lauren Hartny‐Mills; Claire Lacey; Susanna Quer; Matt Sharpe; et al. (Marine Mammal Science, 2026)
Large volumes of passive acoustic data are collected by researchers, governments, and conservationists across the globe to monitor species for population assessments and conservation objectives. An analysis bottleneck often exists due to the lack of tools to process large datasets and identify detected signals to the species level. Deep learning has been shown to enable fast and effective detection of species‐specific vocalizations. This study developed a Risso's dolphin ( Grampus griseus ) binary echolocation click classifier using a Long Short‐Term Memory neural network. This classifier was trained and validated on 872 visually verified single species encounters collected during towed hydrophone surveys, primarily in the Northeast Atlantic. The classifier was subsequently tested on an independent set of 31 h of visually verified data collected from static and drifting recorders in Scottish and English waters, comprising four different delphinid species (including Risso's dolphins) as well as various sources of anthropogenic noise. The best classifier achieved an F1 score of 0.98 (precision 0.96, recall 0.98). While care must be taken when applying deep learning classifiers to new datasets, the performance of this model on independent data highlights its ability to generalize well within the study region, even when using data collected on different recording platforms.

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Healing country together: A seagrass restoration case study from Gathaagudu (Shark Bay) - Elizabeth A. Sinclair; John Statton; Rachel Austin; Martin F. Breed; Richard Cross; Alex Dodd; Amrit Kendrick; Siegfried L. Krauss; Bianca McNeair; Nykita McNeair; Sean McNeair; Marika Oakley; et al. (Ocean & Coastal Management, 2024)

The ties that bind: how trees can enhance agroecological transitions - Marney E. Isaac; F. Sinclair; G. Laroche; A. Olivier; A. Thapa (Agroforestry Systems, 2024)
Agricultural systems have a long history of responding to various economic and socio-political forces, including supply and demand, political preferences and power inequalities. Our current food system continues to respond to contemporary forces with a call for sustainable transformations in the face of increased pressure and competition over resources, severe consequences of climatic change, widespread degradation of land and water resources, and the accelerating loss of biodiversity. Both agroforestry and agroecology have evolved as approaches to agricultural management that focus on the application of ecological principles to achieve sustainable agriculture. Agroecological principles are designed to engage with the entire agrifood system, for instance identifying broad participation and involving a diversity of actors and knowledge systems. Agroecological approaches to production have significant historical and contemporary links to agroforestry approaches, but not all agroecology involves trees and not all agroforestry is in line with agroecological principles. Drawing on (1) a literature review, (2) case studies on the agroforestry and agroecology nexus presented at the 5th World Congress on Agroforestry (WCA), and (3) audience responses to statements presented at the Congress, we explore the two main ways that agroforestry and agroecology come together: agroforestry that encompasses agroecological principles and agroecological transitions that involve trees. We review the status of agroecology, the functions specific to agroforestry that can enhance the achievement of agroecological outcomes, the tensions between simple agroforestry systems and agroecology, and the larger potential of multidimensional sustainability of agroforestry with the inclusion of agroecological principles. We also present the level of agreement on four key statements about the agroforestry-agroecology nexus enumerated at the WCA. It is clear that some features of agroforestry operationalize agroecological principles that aim to transition away from monocultures and the use of environmentally disruptive agrochemicals, and toward strengthening biodiversity and resilience. Yet, much remains to be done to enhance agroecological principles more fully in framing agroforestry practices and to incorporate trees within agroecological practices. Pathways to strengthen the nexus of agroforestry and agroecology are proposed, which focus on the role of trees in multifunctionality and resilience and using agroecological principles related to knowledge sharing and equity to enrich agroforestry practices.

Economic values for ecosystem services: A global synthesis and way forward - L.M. Brander; R. de Groot; J.P. Schägner; V. Guisado-Goñi; V. van 't Hoff; S. Solomonides; A. McVittie; F. Eppink; M. Sposato; L. Do; A. Ghermandi; M. Sinclair; et al. (Ecosystem Services, 2024)

Measuring Food Security among American Indian and Alaska Native Adults: Validity Evidence Supports the Use of the US Department of Agriculture Module - Cassandra J. Nguyen; Brian F. French; Tara L. Maudrie; Gary L. Ferguson; Valarie Blue Bird Jernigan; Ka`imi A. Sinclair (Journal of the Academy of Nutrition and Dietetics, 2023)

Polanyi adsorption potential theory for estimating PFAS treatment with granular activated carbon - Jonathan B. Burkhardt; Adam Cadwallader; Jonathan G. Pressman; Matthew L. Magnuson; Antony J. Williams; Gabriel Sinclair; Thomas F. Speth (Journal of Water Process Engineering, 2023)

Regenerated trees in farmers’ fields increase soil carbon across the Sahel - J. Bayala; J. Sanou; H. R. Bazié; R. Coe; A. Kalinganire; F. L. Sinclair (Agroforestry Systems, 2020)

Enhancing maize productivity in agroforestry systems through managing competition: lessons from smallholders’ farms, Rift valley, Kenya - J. Nyaga; C. W. Muthuri; E. Barrios; I. Öborn; F. L. Sinclair (Agroforestry Systems, 2019)

Water–fat MRI in a hibernator reveals seasonal growth of white and brown adipose tissue without cold exposure - Amanda MacCannell; Kevin Sinclair; Lannette Friesen-Waldner; Charles A. McKenzie; James F. Staples (Journal of Comparative Physiology B, 2017)

A review of contemporary patterns of endemism for shallow water reef fauna in the Red Sea - Joseph D. DiBattista; May B. Roberts; Jessica Bouwmeester; Brian W. Bowen; Darren J. Coker; Diego F. Lozano‐Cortés; J. Howard Choat; Michelle R. Gaither; Jean‐Paul A. Hobbs; Maha T. Khalil; Marc Kochzius; Robert F. Myers; et al. (Journal of Biogeography, 2016)
Aim The Red Sea is characterised by a unique fauna and historical periods of desiccation, hypersalinity and intermittent isolation. The origin and contemporary composition of reef‐associated taxa in this region can illuminate biogeographical principles about vicariance and the establishment (or local extirpation) of existing species. Here we aim to: (1) outline the distribution of shallow water fauna between the Red Sea and adjacent regions, (2) explore mechanisms for maintaining these distributions and (3) propose hypotheses to test these mechanisms. Location Red Sea, Gulf of Aden, Arabian Sea, Arabian Gulf and Indian Ocean. Methods Updated checklists for scleractinian corals, fishes and non‐coral invertebrates were used to determine species richness in the Red Sea and the rest of the Arabian Peninsula and assess levels of endemism. Fine‐scale diversity and abundance of reef fishes within the Red Sea were explored using ecological survey data. Results Within the Red Sea, we recorded 346 zooxanthellate and azooxanthellate scleractinian coral species of which 19 are endemic (5.5%). Currently 635 species of polychaetes, 211 echinoderms and 79 ascidians have been documented, with endemism rates of 12.6%, 8.1% and 16.5% respectively. A preliminary compilation of 231 species of crustaceans and 137 species of molluscs include 10.0% and 6.6% endemism respectively. We documented 1071 shallow fish species, with 12.9% endemic in the entire Red Sea and 14.1% endemic in the Red Sea and Gulf of Aden. Based on ecological survey data of endemic fishes, there were no major changes in species richness or abundance across 1100 km of Saudi Arabian coastline. Main conclusions The Red Sea biota appears resilient to major environmental fluctuations and is characterized by high rates of endemism with variable degrees of incursion into the Gulf of Aden. The nearby Omani and Arabian Gulfs also have variable environments and high levels of endemism, but these are not consistently distinct across taxa. The presence of physical barriers does not appear to explain species distributions, which are more likely determined by ecological plasticity and genetic diversity.

Diversity enhances carbon storage in tropical forests - L. Poorter; M. T. van der Sande; J. Thompson; E. J. M. M. Arets; A. Alarcón; J. Álvarez‐Sánchez; N. Ascarrunz; P. Balvanera; G. Barajas‐Guzmán; A. Boit; F. Bongers; F. A. Carvalho; et al. (Global Ecology and Biogeography, 2015)
Aim Tropical forests store 25% of global carbon and harbour 96% of the world's tree species, but it is not clear whether this high biodiversity matters for carbon storage. Few studies have teased apart the relative importance of forest attributes and environmental drivers for ecosystem functioning, and no such study exists for the tropics. Location Neotropics. Methods We relate aboveground biomass ( AGB ) to forest attributes (diversity and structure) and environmental drivers (annual rainfall and soil fertility) using data from 144,000 trees, 2050 forest plots and 59 forest sites. The sites span the complete latitudinal and climatic gradients in the lowland Neotropics, with rainfall ranging from 750 to 4350 mm year −1 . Relationships were analysed within forest sites at scales of 0.1 and 1 ha and across forest sites along large‐scale environmental gradients. We used a structural equation model to test the hypothesis that species richness, forest structural attributes and environmental drivers have independent, positive effects on AGB . Results Across sites, AGB was most strongly driven by rainfall, followed by average tree stem diameter and rarefied species richness, which all had positive effects on AGB . Our indicator of soil fertility (cation exchange capacity) had a negligible effect on AGB , perhaps because we used a global soil database. Taxonomic forest attributes (i.e. species richness, rarefied richness and Shannon diversity) had the strongest relationships with AGB at small spatial scales, where an additional species can still make a difference in terms of niche complementarity, while structural forest attributes (i.e. tree density and tree size) had strong relationships with AGB at all spatial scales. Main conclusions Biodiversity has an independent, positive effect on AGB and ecosystem functioning, not only in relatively simple temperate systems but also in structurally complex hyperdiverse tropical forests. Biodiversity conservation should therefore be a key component of the UN Reducing Emissions from Deforestation and Degradation strateg y.

Farmers in Côte d’Ivoire value integrating tree diversity in cocoa for the provision of ecosystem services - E. Smith Dumont; G. M. Gnahoua; L. Ohouo; F. L. Sinclair; P. Vaast (Agroforestry Systems, 2014)

Benthic macroinvertebrate communities in five rivers of the Coastal Hudson Bay Lowland - F. Chris Jones; Sarah Sinclair; Wendel Keller (Polar Biology, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Reduced inflammatory potential of peritoneal macrophages recruited in mice pretreated with a glycolipid synthesis inhibitor - H. C. Yohe; T. J. Kitzmiller; W. J. Bement; B. E. Dwyer; J. F. Sinclair (Inflammopharmacology, 2006)

Incorporating an environmental stock–recruitment relationship in the assessment of Pacific cod ( Gadus macrocephalus ) - A. F. SINCLAIR; W. R. CRAWFORD (Fisheries Oceanography, 2005)
The robustness of a previously described environmentally mediated stock–recruitment relationship for Pacific cod in Hecate Strait, BC, Canada was tested with 10 yr of additional data. The original analysis tested several alternative hypotheses and concluded that water transport through Hecate Strait, as indicated by sea level height, coupled with cod spawning biomass formed the best model. The present analysis indicates the relationship held through the 1990s. The implications of variation in sea level on stock production were investigated with a delay‐difference stock production model that included an environmentally mediated stock–recruitment relationship. The model predicted that the maximum fishery yield would vary between 1750 and 3670 t yr −1 over the observed range of sea level height, and the estimated unsustainable fishing mortality during periods of low productivity would be only 0.5 times that in periods of high productivity.

Landscape scale, heterogeneity, and the viability of Serengeti grazers - John M. Fryxell; John F. Wilmshurst; Anthony R. E. Sinclair; Daniel T. Haydon; Robert D. Holt; Peter A. Abrams (Ecology Letters, 2005)
Species persistence can be threatened by substantial temporal variation in food resources over time. On the other hand, spatial heterogeneity in resources at the landscape scale might allow mobile consumers to compensate for temporal variability in resource availability at the local scale. We evaluated this hypothesis, using an extensive data set on foraging, grass growth, and movement by Thomson's gazelles living on the Serengeti Plains. Here we show that modelled populations of Thomson's gazelles can only persist under Serengeti conditions in the face of observed levels of rainfall stochasticity by making adaptive movements to take advantage of ephemeral spatial distributions of food resources. More importantly, our models suggest that Thomson's gazelles in Serengeti require unrestricted access to relatively large areas of grassland (> 1600 km 2 ) to guarantee long‐term persistence, particularly when there is positive spatial autocorrelation in resource abundance, as is the case in Serengeti. If this proves to be true for other species and/or other systems, then understanding of complex behavioural responses to spatially and temporally heterogeneous food supplies may be essential to successful conservation of grazing herbivores.

A Proactive Approach Can Make Site Remediation Less Expensive - Gontran F. Bage; Réjean Samson; Bernard Sinclair-Desgagné (Environmental Management, 2004)

A global assessment using PCR techniques of mycorrhizal fungal populations colonising Tithonia diversifolia - R. A. Sharrock; F. L. Sinclair; C. Gliddon; I. M. Rao; E. Barrios; P. J. Mustonen; P. Smithson; D. L. Jones; D. L. Godbold (Mycorrhiza, 2004)

A Technicoeconomic Approach for theSelection of a Site Remediation Strategy--Part B: Model Application - GONTRAN F. BAGE; RÉJEAN SAMSON; BERNARD SINCLAIR-DESGAGNÉ (Environmental Management, 2003)

A Technicoeconomic Approach for the Selection of a Site Remediation Strategy--Part A: Theory - GONTRAN F. BAGE; RÉJEAN SAMSON; BERNARD SINCLAIR-DESGAGNÉ (Environmental Management, 2002)

On-farm evaluation of the establishment of clonal rubber in multistrata agroforests in Jambi, Indonesia - S. E. Williams; M. van Noordwijk; E. Penot; J. R. Healey; F. L. Sinclair; G. Wibawa (Agroforestry Systems, 2001)

Productivity and profitability of multistrata organic versus conventional coffee farms in Costa Rica - A. E. Lyngbæk; R.G. Muschler; F. L. sinclair (Agroforestry Systems, 2001)

Characterization of multistrata silvopastoral systems on seasonally dry pastures in the Caribbean Region of Colombia - Y. S. Cajas-Giron; F. L. Sinclair (Agroforestry Systems, 2001)

Growth variability in a Senegalese provenance of Acacia nilotica ssp. tomentosa - E. Wolde-Mieskel; F. L. Sinclair (Agroforestry Systems, 2000)

Cod and haddock spawning on Georges Bank in relation to water residence times - F. H. Page; M. Sinclair; C. E. Naimie; J. W. Loder; R. J. Losier; P. L. Berrien; R. G. Lough (Fisheries Oceanography, 1999)
The seasonal and geographical patterns of spawning for Georges Bank cod ( Gadus morhua ) and haddock ( Melanogrammus aeglefinus ) are estimated using composite distributions of stage I eggs derived from the Marine Resources Monitoring, Assessment and Prediction (MARMAP) data set (1977–1987). The inferred mean spawning locations are compared with patterns in particle residence times derived from a three‐dimensional prognostic circulation model that estimates the tidal and seasonal mean circulation. The comparisons indicate that cod and haddock spawning occurs at times and locations characterized by model residence times in excess of 35 d. The results are discussed in the context of fish population regulation theory, particularly the member/vagrant hypothesis and the concept of abundance‐dependent vagrancy.

Incorporation of indigenous knowledge and perspectives in agroforestry development - D. H. Walker; F. L. Sinclair; B. Thapa (Agroforestry Systems, 1995)

Incorporation of indigenous knowledge and perspectives in agroforestry development - B. Thapa; F. L. Sinclair; D. H. Walker (Agroforestry Systems, 1995)